Inulin promotes appetite in mice by regulating the gut microbiota under conditions of rapid entry to the plateau - Xiaoli Li; Shengcai Wu; Xiaonan Chen; Jian Chen; Bao Liu; Xianshuai Liang (PLoS ONE, 2025)
The objective of this study was to examine the mechanism of inulin by regulating the gut microbiota under conditions of rapid entry to the plateau stage. Fifty 7-week-old SPF-grade C57BL/6J male mice were used as experimental subjects and analysed. This study compared the structural and functional characteristics of food intake, body weight changes, serum appetite hormone levels, and intestinal flora of mice in different doses of inulin intervention and control groups in two distinct environments: plains and the rush-into plateau. The results demonstrated that inulin influenced the functional characteristics of the gut microbiota of mice in terms of energy production, conversion, carbohydrate transport, and metabolism. Furthermore, inulin enhanced the secretion of appetite hormones, resulting in appetite promotion under acute plateau conditions by increasing the relative abundance of beneficial bacteria. In addition, inulin significantly improved the body weight of mice under plateau conditions, particularly in the mid- and high-dose groups of inulin-treated mice.